VARIASI KONSENTRASI GULA PADA FERMENTASI CINCALUK SEBAGAI RANCANGAN BOOKLET PADA MATERI BIOTEKNOLOGI KONVENSIONAL SMA - Surani Ariyana; Imam Mahadi; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
bstract: This research was conducted to identify variation of sugarconcentration on fermentation cincaluk rebon shrimp (Acetes erythraeus) and the designof Booklet of senior high school grade XII conventional biotechnology materials in Juni– September 2021. This research carried out in two stages: they are the experimentalstage: variation of sugar concentration on fermentation cincaluk rebon shrimp (Aceteserythraeus) and the designing stage of the Booklet: the analysis of the potentialdevelopment of senior high school grade XII conventional biotechnology material forteaching. The research used the experimental method by conducting experiments in theLaboratory of the Faculty of Fisheries and Marine Sciences Riau University, Pekanbaru.Sampling was carried out with a completely randomized design (CRD) consisting of 5treatments and 3 replications. The parameters in this research were water content,protein content and pH. Based on the results of Analysis of variance (Anova) at the levelof 5%, Showed that the fermentation of rebon shrimp with different sugar concentrationssignificantly affected the quality of cincaluk rebon shrimp (Acetes erythraeus). Givingsugar with a concentration of 15% produces the best quality of rebon shrimp cincalukand based on the analysis of potential research results variations in sugar concentrationin cincaluk fermentation can be used as a student guide booklet design on biotechnologymaterial for senior high school grade XII on the subject matter of conventionalbiotechnology products.Key Words: Cincaluk Fermentation, Sugar, Booklet